2022
DOI: 10.1097/mat.0000000000001787
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of COVID-19 Patients Requiring Extracorporeal Membrane Oxygenation During the Three Epidemic Waves

Abstract: de dominiCis, ‡ VinCent jounieaux, § pasCal Berna, ¶ herVé dupont,* osama aBou-araB,* and yazine mahjouB* Clinical presentation and mortality of patients treated with extracorporeal membrane oxygenation (ECMO) for COVID-19 acute respiratory distress syndrome (CARDS) were different during the French epidemic waves. The management of COVID-19 patients evolved through waves as much as knowledge on that new viral disease progressed. We aimed to compare the mortality rate through the first three waves of CARDS pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…However, other factors, including steroid-resistant disease and changes in clinical management, should not be discarded. 1 Dr. Dandel also suggested that right ventricular (RV) failure may be the primary cause of the high mortality rate of our ECMO patients observed during the second wave. Unfortunately, no precise and objective data supports this hypothesis in our series.…”
Section: To the Editormentioning
confidence: 97%
See 1 more Smart Citation
“…However, other factors, including steroid-resistant disease and changes in clinical management, should not be discarded. 1 Dr. Dandel also suggested that right ventricular (RV) failure may be the primary cause of the high mortality rate of our ECMO patients observed during the second wave. Unfortunately, no precise and objective data supports this hypothesis in our series.…”
Section: To the Editormentioning
confidence: 97%
“…We thank Dr. Dandel for his interest in our previously published article. 1 We acknowledge that the pathogenicity of dominant SARS-COV-2 "variants of concern" during the second wave (Delta variant) may partially explain the higher mortality observed during the second wave. However, other factors, including steroid-resistant disease and changes in clinical management, should not be discarded.…”
Section: To the Editormentioning
confidence: 99%
“…I read with interest the study by Beyls et al . 1 which compared the different clinical characteristics and outcomes of patients with COVID-19–related respiratory distress syndrome (CARDS) requiring veno-venous extracorporeal membrane oxygenation (VV-ECMO) during the three epidemic waves of COVID-19 in France. Despite the increasing knowledge on the particularities of severe COVID-19 and the growing experience in the management of severe CARDS, that study revealed a massive increase in the 90 day mortality of patients undergoing VV-ECMO during the second epidemic wave.…”
Section: To the Editormentioning
confidence: 99%
“…, Alpha/B.1.1.7, Beta/B.1.351 and Gamma/P.1) and the Omicron/B1.1.529 variant which became the dominant VOC during third wave. 2,3 The excessively high mortality rate ( i.e ., 85.7% 1 ) of patients supported by ECMO during the second wave deserves particular attention because a renewed appearance of more pathogenic VOCs cannot be ruled out.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation